Show Me, Tell Me, Encourage Me: The Effect of Different Forms of Feedback on Resistance Training Performance. Issue 11 (November 2020) - Weakley, Jonathon; Wilson, Kyle; Till, Kevin; Banyard, Harry; Dyson, James; Phibbs, Padraic; Read, Dale; Jones, Ben
Abstract : Abstract: Weakley, J, Wilson, K, Till, K, Banyard, H, Dyson, J, Phibbs, P, Read, D, and Jones, B. Show me, tell me, encourage me: The effect of different forms of feedback on resistance training performance. J Strength Cond Res 34(11): 3157–3163, 2020—When performing resistance training, verbal kinematic feedback and visual kinematic feedback are known to enhance performance. In addition, providing verbal encouragement can assist in the attenuation of fatigue. However, the effects of these forms of feedback have never been compared. Consequently, this study aimed to quantify the effects of verbal kinematic feedback and visual kinematic feedback, and verbal encouragement on barbell velocity during the back squat. Furthermore, changes in performance were related to individual-reported conscientiousness. Twelve semiprofessional rugby union players volunteered to participate in the study that consisted of the subjects completing a set of the barbell back squat across 4 conditions (i.e., no-feedback [control], verbal feedback of kinematic information [verbal], visual feedback of kinematic information [visual], and verbal encouragement [encouragement]). In addition, participants completed a questionnaire before the study to assess conscientiousness. Magnitude-based inferences were used to assess differences between conditions, whereas Spearman's rank correlation coefficient was used to assess relationships between conscientiousness and changes in barbell velocity. All 3 forms of feedback showed almost certain improvements in barbell velocity, while differences between interventions were likely to very likely trivial. Changes in barbell velocity showed small to large inverse relationships with conscientiousness. These findings suggest that practitioners should supply kinematic feedback (verbally or visually) or, when technology is not available, provide athletes with encouraging statements while resistance training. Verbal encouragement may be of greatest benefit for individuals who demonstrate low levels of conscientiousness. Given these findings, practitioners are advised to use either technology or verbal encouragement to manipulate acute training outcomes.